Exploring The Inhibition of SARS-COV-2 PLpro: Docking and Molecular Dynamics Simulation of Flavonoid in Red Fruit Papua and Its Derivatives - Ananto, Agus Dwi; Pranowo, Harno Dwi; Haryadi, Winarto; Prasetyo, Niko (Molekul, 2024)
In early 2024, Covid-19 witnessed a substantial decline in cases. Nevertheless, with lingering cases and fatalities persisting, it remains crucial to focus on research to develop patented medicines to inhibit the spread of this virus effectively. This study focuses on the Papain-like protease (PLpro) of SARS-CoV-2 because of its crucial role in the viral life cycle, where it is vital for processing precursor proteins into functional components required for viral replication and propagation. This study investigated the inhibitory potential of flavonoid compounds derived from red fruit (Pandanus conoideus Lam) and their derivatives against SARS-CoV-2 PLpro. Employing an in silico approach through molecular docking and MD simulation, internal validation was conducted by redocking the native ligand 100 times, resulting in an average RMSD of 0.228. The Molecular Docking stage conducted for all flavonoid compounds found in red fruit revealed that Quercetin 3′-glucoside exhibited a binding energy of -8.2440 Kcal/mol, surpassing its comparators, remdesivir and paxlovid, which recorded binding energies of -8.2590 Kcal/mol and -7.2170 Kcal/mol, respectively. Consequently, Quercetin 3′-glucoside was selected as a reference compound for identifying derivative compounds. Subsequently, a derivative compound coded DN5 (2-hydroxy-5-(3,5,7-trihydroxy-4-oxo-4H-chromen-2-yl)phenyl 2-methoxybenzoate) was obtained, demonstrating a higher binding energy than the reference compound, remdesivir, and paxlovid, with a value of -8.9300 Kcal/mol. Molecular dynamic simulations over 100 ns at 300 K further validated the stability of DN5's structure, supported by the presence of hydrogen bonds, van der Waals bonds, and several other bonds, underscoring its potential to inhibit SARS-CoV-2 PLpro and positioning it as a promising candidate for drug development. Keywords: Docking, MD Simulation, red fruit, SARS-CoV-2 PLpro